Surgical Conversion for Initially Unresectable Locally Advanced Hepatocellular Carcinoma Using a Triple Combination of Angiogenesis Inhibitors, Anti-PD-1 Antibodies, and Hepatic Arterial Infusion Chemotherapy: A Retrospective Study - Zhang, Jinliang; Zhang, Xihao; Mu, Han; Yu, Ge; Xing, Wenge; Wang, Lu; Zhang, Ti (Frontiers in Oncology, 2021)
Background: Recent research has shown that selected patients with initially unresectable hepatocellular carcinoma (HCC) are able to achieve conversion to resectable disease through systemic or local therapy. Combination regimens comprised of drugs with different mechanisms of action have shown better outcomes than single-drug or single-approach-based treatments; however, to date, combination regimens investigated as part of conversion therapy strategies have been two drug combinations with reported issues of relatively low surgical conversion and objective response rates. In this study, we investigated the efficacy and safety of triple combination therapy with angiogenesis inhibitors, programmed death-1 inhibitors and hepatic arterial infusion chemotherapy for surgical conversion of advanced HCC. Methods: This was a single-center, retrospective, single-arm study of patients with unresectable HCC who received at least one cycle of triple combination therapy with an oral anti-angiogenic drug, programmed death-1 inhibitors and hepatic arterial infusion chemotherapy between August 2019 and August 2020. Endpoints included the overall response rate (ORR), surgical conversion rate, time to response and safety. Treatment response was assessed using the modified Response Evaluation Criteria in Solid Tumors (mRECIST) and RECIST v1.1. Results: In total, 34 patients were included in this study, of whom 25 completed treatment evaluation. The best ORR was 96.0% (24/25); 48.0% (n = 12) had a complete response, 48.0% (n = 12) had a partial response, and 4.0% (n = 1) had stable disease. The median time to response was 50.5 (95% CI, 31.02–64.00) days and the surgical conversion rate was 60% (15/25). Of the 25 patients, 56.0% (n = 14) received surgical resection and 28.0% (n = 7) had a pathologic complete response. Toxic side effects were manageable. Conclusion: A triple combination therapy regimen of angiogenesis inhibitors, programmed death-1 inhibitors and hepatic arterial infusion chemotherapy showed significant therapeutic effect with an extremely high surgical conversion rate in patients with initially unresectable HCC.